Land-River Interface Management Semi-Structured Interview Data - Grabowski, Robert C.; Azhoni, Azhoni (Cranfield University, 2022)
About the data: The data contained in this archive are collected through semi-structured interviews from officials in key organizations involved in land-river interface management in India. The interviews were conducted through online video conferencing and recorded which were later transcribed verbatim for analyzing the key challenges of land-river interface management in India. The Garret ranking data was collected at the end of the interviews and marked in the form by the interviewer. The research was conducted as part of a collaborative NERC Towards a Sustainable Earth project (2019-2022), with direct funding from the Indian Department of Biotechnology. File names: Each interview transcript is in different files with the file name indicating the type organizations the interview respondents represent, viz; Academic Institutions (AI), Central Government Agencies (CGA), Central Government Ministries (CGI), Non-governmental organizations (NG), and State Government Departments (SG). This files are being archived for future reference and for providing transparency to the research data.
Keywords: Interview'; 'India'